Visualizing mitochondria and mouse intestine with a fluorescent complex of a naphthalene-based dipolar dye and serum albumin. Issue 34 (29th July 2020) - An, Jong Min; Moon, Heejo; Kim, Yejin; Kang, Sangrim; Kim, Youngseo; Jung, Yuna; Park, Sungnam; Verwilst, Peter; Kim, B. Moon; Kang, Jae Seung; Kim, Dokyoung
Abstract : A fluorophore–protein complex for the visualization of mitochondria and the mouse intestine was developed. The complex formation of a naphthalene-based dipolar dye and serum albumin was identified and its imaging applications were investigated. Abstract : We have explored a new research field of fluorophores through the manipulation of fluorophore-binding proteins. The development of a new imaging agent for tracing a specific organelle or a particular site within a living organism has been of great interest in the field of basic science as well as translational medicine. In this work and for the first time, we will disclose a new naphthalene-based dipolar dye and its complex, with serum albumin (SA), and show their applicability for the selective imaging of mitochondria in cells and the intestine in a mouse. The SA-binding dipolar dye, IPNHC, was synthesized straightforwardly, and we identified its photophysical properties and binding mode with SA. IPNHC–SA complex showed a bright emission in the blue wavelength range with a high quantum yield and stability. In the fluorescence imaging study, bright fluorescence images of mouse intestines were observed under a UV light, as well as two-photon (TP) deep tissue imaging after intravenous injection of IPNHC and IPNHC–SA complex. The present findings hold great promise for the application of the fluorescent complex for use in the tracing and tracking of intestine-related diseases at clinical sites.